Sosa, general assumptions, and the skeptical trojan horse - Modesto Gómez-Alonso (Trans/Form/Ação, 2022)
For many hinge epistemologists, general, background assumptions are principles that help providing default or presumptive justification to our empirical beliefs. However, the ‘blanketing’ nature of a priori arguments to the end of supporting the rationality of general assumptions might be seen as the Trojan horse through which radical scepticism threatens the common sense picture of the world. Sosa’s recent distinction between background presuppositions and domain-defining conditions, as well as his claim that agents are not negligent for dismissing global scenarios as irrelevant to epistemic normativity, are instrumental to avoid an epistemic construal of über hinges, and thus, to a reassessment of the function they really perform in regards to ordinary practices of judgment.